EFEKTIVITAS MANAJEMEN IKLIM KELAS DALAM MENINGKATKAN PRESTASI BELAJAR SISWA DI SD NEGERI 06 LUBUK KELIAT, SUMATERA SELATAN - Akhmad Saputra, Ade; Della Saputri, Leura (An-Nadzir : Jurnal Manajemen Pendidikan Islam, 2024)
The purpose of this research is to find out how class management creates creative, innovative, fun, and interesting learning effectiveness towards learning at SD Negeri 06 Lubuk Keliat Ogan Ilir Regency. A conducive learning situation needs to be maintained so that the growth and development of students are effective and efficient. Therefore, improving the quality of learning in the classroom must be carefully considered because it is one of the supporting factors for improving the quality of education. The research method used is Descriptive in Qualitative form. The subject of this research is SD Negeri 06 Lubuk Keliat Ogan Ilir Regency. Data collection techniques and tools using live communication techniques, direct observation techniques, and documentation studies. The study found that classroom management plays an important role in improving student learning performance at SD Negeri 06 Lubuk Keliat. The result of this study indicates that teachers who are able to lead learning well are able to create a learning environment that supports and encourages students to be active in class and has a positive impact on improving learning outcomes.